The Impact of Perception of Public Relations on the Fintech Lending Customer Loyalty - Lovis, Kevin Zaprilan (JURNAL KOMUNIKASI INDONESIA, 2021)
Brand image and customer trust are important to establish customer loyalty. In this era of intense business competition, it is important to pay attention to customer loyalty. Many things can be done to build customer loyalty, including managing a good brand image and maintaining customer trust in the company through communication efforts from public relations to form a good perception of public relations. Specifically for the fintech lending industry which is engaged in finance and technology, image and trust are two important things that also need to be considered to gain customer loyalty. This study aimed to measure the direct and indirect effect of perception of public relations on customer loyalty through brand image and customer trust in the fintech lending industry. Applying a positivist paradigm and quantitative approach, this research was conducted on 400 research samples. Method for collecting data was a survey by questionnaire. The results was analysed using SPSS path analysis and showed that the perception of public relations did not affect customer loyalty directly and significantly. Furthermore, the results of the study also showed that the perception of public relations affected customer loyalty indirectly through brand image and customer trust partially. However, indirect influence through brand imagewas better than customer trust.